Conflict of Legislative and Judicial Jurisdiction Regarding the Protection of Persons with Disabilities : An Analytical Study - Hasan, Daraf (Journal of Legal Sciences, 2026)
A disability may prevent a person from carrying out essential daily tasks, including managing their finances, claiming their inheritance after the death of their ancestor, or entering into contracts, especially if the disability is intellectual or mental, or if it is a severe and prolonged physical injury. In such cases, the person needs legal representation, such as a guardian, trustee, or custodian, to manage their financial and personal affairs ("guardianship of property and person"). However, this representation can be exploited, as the authority granted to these individuals may be abused by misappropriating the disabled person's assets, transferring them to others, or smuggling them out of the country to deprive them of their rights. This is done by exploiting the disabled person's vulnerability and inability to defend their assets or claim their rights in court. Therefore, this person needs legal and judicial protection through the application of the most favorable law. The judge must apply the rules that are necessary for the protection of persons with disabilities whenever their rights fall within the scope of such rules. In the absence of such rules, the judge must apply the relevant international substantive rules that govern the rights of persons with disabilities, excluding any law that prohibits them from exercising these rights. This is one of the rights of the person, and the importance of judicial protection for the person with a disability is demonstrated by relying on the officer who provides protection for this person and his money, while taking the necessary measures regarding the money of the person with a disability to prevent the deputy or others from disposing of it.